Modelling factors influencing brand experience and its consequences on Malaysia’s national automotive brands / Wan Nadiah Mohd Nadzri - Mohd Nadzri, Wan Nadiah (Institute of Graduate Studies, UiTM, 2017)
Automotive players that neglects post purchase have suffered poor sales as consumers no longer tolerate with mediocre services. Not only automotive players produced low quality car but also bad operational facilities when servicing their car. Resulting in low brand experience and consumers are left unsatisfied with their car purchase. However, brand experience has received enormous attention by researchers over the decades. Evidently, past research revealed that brand experience plays a vital role in understanding desired outcome such as brand trust, brand loyalty, brand community, brand attachment and brand engagement. In fact, brand experience has been in the spotlight by both academic and practitioners within design literature, thus bringing two perspectives together. Mehrabian and Russell theory was employed as the theoretical foundation in developing present conceptual framework. This study emphasizes on using PADI model as a tool to measure the new brand experience scale. The significance of this study, lies in the fact that, it attempts to examine the antecedents of brand experience such as servicescape, brand image and servicescape which in turn investigates the consequences within Malaysia national automotive industry.